The book of pizza : recipes for every pizza maker - Philip, Martin; Tamarkin, David; Battilana, Jessica; Boytsova, Yekaterina; Salerno, Ryan (Simon Element, 2026)
"From the team behind the #1 New York Times bestseller The King Arthur Baking Company Big Book of Bread, comes the definitive book dedicated to the key elements of making pizza in any home oven, countertop pizza oven, or backyard oven or grill."--Amazon.